Rigid Bronchoscopy - Alraiyes, Abdul Hamid; Machuzak, Michael S. (Seminars in Respiratory and Critical Care Medicine, 2014)
The purpose of this article is to provide an introduction to rigid bronchoscopy (RB). We will briefly discuss its history, evolution, and resurgence while we highlight its versatility and usefulness for today's interventional pulmonologist and thoracic surgeon. Despite being one of the earliest pulmonary procedures described, RB is still an important technique. Advances in thoracic medicine have made this skill critical for a fully functional interventional pulmonary program. If the interventional pulmonologist of this century is to be successful, he or she should be facile in this technique. Despite the availability of RB for decades, the invention of flexible bronchoscopy in 1966 led to a significant downturn in its usage. The growth of the interventional pulmonology field brought RB back into the spot light. Apart from the historic role of RB in treatment of central airway lesions and mechanical debulking of endobronchial lesions, RB is the key instrument that can adapt modern therapeutic tools such as laser, argon plasma coagulation, electrocautery, cryotherapy, and stent deployment. Performing RB requires proper preprocedure preparation, exceptional understanding of upper airway anatomy, specific hand–eye coordination, and open communication between the bronchoscopist and the anesthesiologist. These skills can be primarily learned and maintained with repetition. This article will review information relevant to this technique and lay a foundation to be built upon for years to come.
Keywords: rigid bronchoscopy; rigid intubation; endobronchial tumor; therapeutic rigid bronchoscopy; foreign body extraction; massive hemoptysis